MASYARAKAT EKONOMI ASEAN (MEA) SETELAH TIGA TAHUN PENGIMPLEMENTASIAN DI INDONESIA - Gita Paramita Agustin (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2018)
The ASEAN Economic Community (AEC) is a community of ASEAN countries having a vision and mission to further enhance the welfare of ASEAN countries. The AEC makes the boundaries that were more complicated and difficult to run easier and there are almost no restrictions at all in terms of the economy. There are several advantages and disadvantages with the enactment of the AEC in Indonesia. The AEC is expected to further improve the economy in Indonesia. The level of export imports, poverty rates and the number of unemployed and the level of income per capita and gross domestic product are indicators in measuring the economic development in a country. To find out the success of the AEC which has been running for 3 years, this study will compare these indicators before and after the enactment of the AEC in Indonesia. Keywords: ASEAN Economic Community (AEC), import exports, poverty rates, unemployment, per capita income and gross domestic product.